Digitate and capitate soft corals (Cnidaria: Octocorallia: Alcyoniidae) from Western Australia with reports on new species and new Australian geographical records - Bryce, Monika; Poliseno, Angelo; Alderslade, Philip; Vargas, Sergio (Zootaxa, 2015)
We report on digitate and capitate Octocorallia within the genera Parasphaerasclera McFadden & Ofwegen, 2013, Eleutherobia Pütter, 1900, Sphaerasclera McFadden & Ofwegen, 2013, and Paraminabea Williams & Alderslade, 1999 from tropical Western Australian waters. Three new species (Parasphaerasclera kimberleyensis, Eleutherobia australiensis, Eleutherobia imaharai) are described, with a discussion of their taxonomic placement in the light of a recent treatment of the genus Eleutherobia and related taxa by McFadden & Ofwegen (2013). In addition, range extensions for three species are reported, Parasphaerasclera grayi (Thomson & Dean, 1931) known from Indonesia and the Pacific Ocean, Eleutherobia somaliensis Verseveldt & Bayer, 1988 from Somalia, and Eleutherobia splendens (Thomson & Dean, 1931) recorded from Indonesia and the Philippines. Additionally, one new Australian geographical record (Sphaerasclera flammicerebra) (Williams, 2003) with a known distribution from Palau to Mauritius, has been included. We complement morphological taxonomy with molecular data (mtMutS, 28S rDNA) to analyse and clarify phylogenetic placement of these species. The mitochondrial mtMutS phylogeny supported Eleutherobia, Paraminabea, Parasphaerasclera and Sphaerasclera as distinct monophyletic genera. Phylogenetic analyses based on 28S rDNA lacked resolution and were largely unresolved. Additionally, the molecular data corroborated our proposed morphological hypothesis of the placement of the new species P. kimberleyensis sp. nov. with no anthocodial armature in the genus Parasphaerasclera, and the assignment of the new species, E. australiensis sp. nov. and E. imaharai sp. nov., with distinct polyps sclerites in the genus Eleutherobia.